LOMBER DİSK HERNİSİNDE IDET (İNTRADİSKAL ELEKTROTERMAL TERAPİ) ANÜLOPLASTİ UYGULANMIŞ HASTALARDAKİ SONUÇLAR: RETROSPEKTİF ÇALIŞMA - İLERİ, ABDURRAHMAN (Fırat Üniveristesi, 2017)
Bel ağrıları, erişkinlerin %80'ini yaşamları boyunca en az bir defa etkileyebilen ve sebep olduğu iş gücü kayıpları yanında tanı ve tedavi prosedürleri açısından değerlendirildiğinde yüksek maliyetlere yol açabilen önemli bir sağlık problemidir ve tedavisi multidisipliner bir yaklaşım gerektirir. Bu çalışmada lomber disk hernisi hastalarında IDET anüloplasti uygulanmasının kliniğimizdeki sonuçlarını değerlendirmek amaçlanmıştır. Fırat Üniversitesi Hastanesi Algoloji Polikliniği'ne başvuran lomber disk hernisi tanısı almış, kronik diskojenik ağrılı, 2012-2014 tarihleri arasında IDET anüloplasti uygulanan hastalar retrospektif olarak değerlendirildi. Çalışma kriterlerini karşılayan 90 hasta çalışmaya dahil edildi. Cinsiyetler açısından yaş, ağrı süresi, preoperatif VAS skorları, postoperatif VAS skorları açısından anlamlı farklılık yoktu (p=0.75). Hastalar en sık (%56,7) bilateral alt ekstremite ağrısıyla kliniğimize başvurdu. Hastalardaki en sık MRG patolojsi rüptür+ bulging (%50), ikinci sıklıkta rüptür+protrüzyon (%28,9) idi. 14 hastanın (%15,5) daha önce herhangi bir tedavi almadığı, 53 hastanın (%58,8) medikal tedavi aldığı ve 23 hastaya (%25,5) TFS uygulandığı tespit edildi.Şikayet seviyelerinin en sık L4-5 (45) ,ikinci sıklıkta L5-S1 (23) olduğu görüldü. İşlem yapılan tüm seviyelerde preoperatif ve postoperatif VAS skorları arasında anlamlı farklılık vardı (p<0.05). Hastaların preoperatif VAS skorları postoperatif VAS skorlarından belirgin yüksekti (p=0,000).. Memnun olmayan hasta sayısı 18 (%20,0), orta derecede memnun olan hasta sayısı 23 (%25,6), iyi derecede memnun olan hasta sayısı 28 (%31,1), mükemmel derecede memnun olan hasta sayısı ise 21 (%23,3) olarak bulundu. Sonuç olarak; IDET anüloplasti genç ve orta yaş hastalarda diskojenik ağrıya karşı tatmin edici sonuçlarla kullanılabilen minimal invazif tekniklerden biridir. Düşük komplikasyon ve yan etki riskine sahiptir. Ancak etkinliğinin daha fazla değerlendirilmesi açısından daha fazla klinik çalışmaya ihtiyaç vardır. Anahtar Kelimeler: Bel ağrısı, Lomber Disk Hernisi, İntervertebral Disk, IDET Anüloplasti

Lower back pain is a major health problem which may affect 80 percent of the adults at least once in a lifetime causing not only labor loss but also increase in diagnostic and therapeutic costs and requires a treatment with a multidisciplinary approach. This study aims to evaluate our clinic's results of IDET annuloplasty applications in patients with lumbar disc herniation. Patients who admitted to Firat University Hospital Algology Clinic for chronic discogenic pain caused by lumbar disc herniation and underwent annuloplasty IDET between 2012-2014 were evaluated retrospectively. Ninety patients who met the study criteria were included in the study. There was no difference between the genders in terms of age, duration of pain, preoperative and postoperative VAS scores (p = 0.75). The patients most frequently (%56.7) referred to our clinic with bilateral lower extremity pain. The most frequent MRG pathology in the patients was rupture + bulging (%50), the second most common rupture + protrusion (%28). 14 patients (15.5%) had not received any previous treatment before, 53 patients (58.8%) had received previous medical treatment and 23 patients (25.5%) had been treated with TFS. The most common discopathy (with 45 patients) was in L4-5 vertebra and the second most common (23 patients) was in L5-S1 vertebra. In patients who were operated, there was a significant difference for all the levels of the spine between preoperative and postoperative VAS scores (P <0.05). Patients' preoperative VAS scores were significantly higher than their postoperative VAS scores (P = 0.000). The number of patients who are not satisfied was 18 (20.0%); the number of patients who are moderately satisfied was 23 (25.6%); the number of patients who are satisfied was 28 (31.1%) and the number of patients who are perfectly satisfied was 21 (23.3%). As a result; IDET annuloplasty is one of the less minimally invasive techniques that can be used with satisfactory results against discogenic pain in young and middle-aged patients. And it has a low risk of side effects and complications. However, there is still need for more clinical trials for further evaluation of efficiency. Keywords: Low back pain, lumbar disc herniation of intervertebral disc, IDET Annuloplasty
Results in patients treated with intradiscal electrothermal therapy (IDET) annuloplasty for lumbar disc herniation: A aretrospective study
Keywords: Anestezi ve Reanimasyon